Coming back to a Commons approach to construct the Great Green Wall in Senegal. (April 2022) - Delay, Etienne; Ka, Abdou; Niang, Khoudia; Touré, Ibra; Goffner, Deborah
Abstract: Since the 1970s, the Sahel region has been struck by severe droughts that has brought suffering to human populations. Scientists also observed declining rainfall leading to desertification in the zone. Against this backdrop, in 2007, several African states launched the international Great Green Wall (GGW) project that aimed to create a strip of forest from Senegal to Djibouti, crossing areas mostly devoted to pastoralism. We examined the social, land tenure and environmental implications of the GGW in Senegal, in the light of policies for pastoral intensification of the zone. The colonial heritage of the foresters from the Senegalese National Green Wall Agency who implement the project on the ground influences how reforestation is managed today. To understand how local populations relate to the space affected by the project and their resources, we organized participatory workshops in four contrasted study sites along the Senegalese portion of the GGW path. Our results show that trees are of great importance for local populations, whether agricultural or pastoral, but even more so in pastoral areas. Despite this, the national and international narrative considers Sahelian pastoralism and overgrazing as strong drivers of desertification. The paradox is that overgrazing is linked to the public policy of boreholes densification. Taking a Commons approach, we show the current and past role played by water in pasture management, and how water accessed by boreholes no longer regulates grazing practices. A Commons approach would pave the way for assisting stakeholders at different levels to favor regreening the Sahel. Highlights: By reforesting for the GGW, Sahelian states strengthen their legitimacy and international discourse around desertification. By hindering human and herd mobility, the GMW plots are a potential source of conflict. By establishing GGW plots, the State is re-establishing its authority in remote areas. By providing unlimited water, boreholes render traditional overgrazing management ineffective. A Commons approach would allow for a renewal of reforestation strategies and rangeland management.